Training And Education of Business Analysis of Tilapia Fish Farming and Golden Fish Spawning with Biofloc System - Kristiany (indonesia), Maria Goreti Eny; Pramono Adi (indoensia) et al, Catur (Fakultas Pertanian_Universitas Tidar, 2025)
This community engagement program aims to empower vocational high school (SMK) students through entrepreneurship training in sustainable aquaculture, particularly focusing on biofloc-based Nile tilapia farming and goldfish hatchery practices. Conducted in collaboration with SMK Negeri Cilebar and held at the Karawang Polytechnic of Marine and Fisheries, the training provided both theoretical knowledge and hands-on experience. Biofloc technology, an efficient aquaculture method using microbial activity to recycle organic waste into fish feed, offers a viable solution for fish farming in limited spaces. Meanwhile, goldfish hatchery, a high-profit upstream aquaculture activity, was introduced to enhance students’ understanding of seed production cycles. The program outcomes include increased student awareness and commitment to applying business analysis in aquaculture, improved practical skills in small-scale fish farming, and the establishment of a cooperative relationship between educational institutions. The initiative not only supports local food security and youth entrepreneurship but also promotes the utilization of Karawang’s abundant aquatic resources through environmentally friendly practicesKeywords: Community empowerment, catfish farming, participatory training, aquaculture, rural entrepreneurship, Mina Sejahtera, Subang